‘Kamrupa’-A new dual chicken variety for farmers of Asom and North-East India - KALITA, N; PATHAK, N; AHMED, M (The Indian Journal of Animal Sciences, 2016)
A dual type multicolored new variety of chicken was developed by crossing Indigenous birds of Asom with a broiler parent PB-2, and a layer parent Dahlem Red, procured from Directorate of Poultry Research, Hyderabad. The present study aimed to study productive and reproductive performance of this variety under intensive and free range system in rural areas of Asom. During the study, body weights of the birds at all stages of growth reared under intensive rearing system were significantly higher than the free range system. The shank length, keel length and breast angle were recorded as 3.98±0.64 cm, 3.21±0.25 cm and 63.75±2.23 degree in intensive system and 4.31±0.98 cm, 3.88±0.76 cm and 62.35±2.54 degree in free range system, respectively. The pullet matured by 20.83 days earlier and laid 20.40 more eggs annually in intensive system compared to that of free range system. The egg weight at 32 weeks and 40 weeks were higher by 1.70 g and 2.66 g in intensive system than that of free range system. The egg quality traits, viz. shape index, albumin index, yolk index, Haugh unit, shell thickness and fertility and hatchability were better in free range system than that of intensive system. Most of the carcass characteristics and survivability of Kamrupa bird were slightly better in intensive system than that of the free range system. From economic point of view, Kamrupa bird’s performance is slightly better in free range system than that of the intensive system.